Inflammasomes and Pyroptosis of Liver Cells in Liver Fibrosis - Gan, Can; Cai, Qiuyu; Tang, Chengwei; Gao, Jinhang (Frontiers in Immunology, 2022)
Inflammasomes are multiprotein complexes that can sense danger signals and activate caspase-1 to mediate pro-inflammatory cytokines release and pyroptotic cell death. There are two main canonical and non-canonical signaling pathways that trigger inflammasome activation. Inflammasomes are expressed and assembled in parenchymal and nonparenchymal cells in response to liver injury in the liver. Additionally, the hepatocytes, biliary epithelial cells (cholangiocytes), hepatic stellate cells (HSCs), hepatic macrophages, and liver sinusoidal endothelial cells (LSECs) contribute to liver fibrosis via different mechanisms. However, the underlying mechanism of the inflammasome and pyroptosis in these liver cells in liver fibrosis remains elusive. This review summarizes the activation and function of inflammasome complexes and then discusses the association between inflammasomes, pyroptosis, and liver fibrosis. Unlike other similar reviewers, we will focus on the effect of inflammasome activation and pyroptosis in the various liver cells during the development of liver fibrosis. We will also highlight the latest progress of pharmacological intervention in inflammasome-mediated liver fibrosis.